Evaluating the attractiveness of different bait formulations for monitoring Liriomyza sativae (Diptera: Agromyzidae) adults - Tamashiro, Luiza Akemi Gonçalves; Oliveira, Regiane Cristina [UNESP]; Pratissoli, Dirceu; Oliveira, Ana Carolina Lopes Francisco de; Piffer, Ana Beatriz Mamedes (Zeppelini Editorial e Comunicacao, 2025)
The growing need for sustainable agricultural practices drives the search for effective alternatives in pest management. Insects like Liriomyza sativae cause significant damage to crops, requiring monitoring and control methods that minimize the use of chemical pesticides. In this context, the use of natural and synthetic attractants for pest capture offers a promising solution while contributing to the preservation of ecological balance. The objective of this work was to study the attractive effect of different formulations for L. sativae adults. The formulations were divided into two groups according to their composition. For group 1, they were based on vinegar and sugar, and for group 2, formulations were based on molasses, invert sugar, hydrolyzed protein, and eugenold. The attractiveness of the formulations was evaluated based on free choice. They were placed in tube-shaped plastic containers and randomly arranged in TNT cages. Evaluations were performed every 48 hours by counting the number of adults in the containers until there was a low capture rate. Data were subjected to analysis of variance testing and means were compared using the Scott-Knott test at 5% significance level. All formulations tested were attractive to adults of L. sativae, with groups 1 and 2 reaching their maximum averages of 55.60 and 68.00 adults, respectively. Both occurred during the second evaluation. Over time, all formulations showed a reduction in capture rate. The use of effective attractants promotes traps that monitor and even control the pest population in a more sustainable way, benefiting the agroecosystem with sustainable agricultural practices. Furthermore, the research expands knowledge about the chemical ecology of insect pests, providing a basis for the chemical communication of these organisms.
Avaliação da atratividade de diferentes formulações de iscas para monitoramento de adultos de Liriomyza sativae (Diptera: Agromyzidae)
Keywords: attractant substances; integrated management; leafminer; miner fly